Comparative clinical and microbiological efficacy of mouthwashes containing 0.2% and 0.12% chlorhexidine - S K Rath; Munishwar Singh (Wolters Kluwer Medknow Publications, 2013)
Background: The main stay of primary and secondary prevention of periodontal diseases has been the control of supra gingival plaque. Acceptable plaque control by mechanical means is difficult to achieve by most individuals, so mouth rinses represent one form of attack on oral microbes and the malodor. Chlorhexidine (CHX) is a broad-spectrum antimicrobial agent known to cause damage to the cell membrane of microorganisms and at higher concentrations causes precipitation and coagulation of the proteins in the cytoplasm of the exposed microbes. The aim of this study is to evaluate and compare the efficacy of 0.12% and 0.2% concentration of CHX gluconate clinically as well as microbiologically. Materials and Methods: The single blind placebo controlled randomized study design comprising of 75 males with an age between 25 years and 50 years were selected from out-patient Department of Periodontics. The subjects were randomly divided into five groups. After baseline clinical and microbiological examination, the groups were subjected to mechanical plaque control with or without mouthwashes containing various concentrations of CHX and placebo. After 90 days the data pertaining to clinical and microbiological parameters were compared to the baseline data so as to compare the efficacy of different concentrations of mouthwashes. Results: The results achieved with the use of 0.2% and 0.12% concentrations of CHX were comparable; taking into consideration of various clinical and microbiological parameters. Conclusion: The study recommends the use of low concentration of (0.12%) CHX for better patient compliance with the optimum clinical results